Exploring needs analysis of English language training: An evidence from small hotel and restaurant employees in Nusa Lembongan, Bali, Indonesia - Ni Luh Nyoman Seri Malini; Ni Wayan Sukarini; Ida Bagus Putra Yadnya; Sang Ayu Isnu Maharani (Indonesian Journal of Applied Linguistics, 2022)
The tourism industry is one of the fastest-growing businesses in Indonesia, especially in Bali which contributes local and national economies. As most of the time English is used to carry out businesses, mastering English plays a significant role in their economic improvement. This study is intended to analyze the specific needs for English in the local tourism industry to prepare a need analysis of English language training for hotel and restaurant employees to empower the local community. The data for this mixed-method design study were taken a set of questionnaires on the needs, functions, and problems of using English in the tourism industry distributed to 36 respondents, observation, and interviews with employees as students and administrators. The collected data were analyzed using Katz’s (2009) simple non-parametric statistics and descriptive-interpretatively narrated. The findings show that most employees consider speaking to be the most important skill to function in their routine work because they need to guide, interact and communicate with (potential) customers, in particular, with foreign tourists visiting tourist attractions throughout the Mushroom Bay area, Nusa Lembongan. Concerning the use of English, they mostly employed English for general conversations, for providing services, and for giving information. The challenges they face in using English include inappropriate words and expressions usage in speech, being unable to understand foreign accents, having inadequate vocabulary in reading, and a lack of grammar knowledge in writing. These findings are used as the basis for developing course plans in English language training for small hotel and restaurant employees.